2013
DOI: 10.1080/03630242.2012.732680
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Perceived Stress and Life Style Leading to Breast Cancer

Abstract: Researchers conducted a study in a Taiwanese medical center from June 2009 to June 2011 to investigate the relations of perceived stress and lifestyle to breast cancer. A total of 157 cases and 314 controls completed a structured questionnaire. Using multiple logistic regression models, high perceived stress (adjusted odds ratio [AOR] = 1.65; 95% confidence interval [CI], 1.10-2.47), less than 1,000 kcal of physical activity expenditure per week (AOR, 2.17; 95% CI, 1.39-3.39), and high intake of fried and stir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 75 publications
1
33
0
1
Order By: Relevance
“…A recent study reported that alcohol drinking was associated with an elevated risk of breast cancer (Odds Ratios = 1.86, 95% Confidence Intervals: 1.02-3.39) (Gao et al, 2013). However, one study showed an inverse association (OR = 0.63; 95%CI: 0.52-0.76) , while another found no relationship between them (OR = 1.50; 95%CI: 0.74-1.02) (Wang et al, 2013). Hence, it is necessary to clarify the association between alcohol drinking and breast cancer risk among Chinese female.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…A recent study reported that alcohol drinking was associated with an elevated risk of breast cancer (Odds Ratios = 1.86, 95% Confidence Intervals: 1.02-3.39) (Gao et al, 2013). However, one study showed an inverse association (OR = 0.63; 95%CI: 0.52-0.76) , while another found no relationship between them (OR = 1.50; 95%CI: 0.74-1.02) (Wang et al, 2013). Hence, it is necessary to clarify the association between alcohol drinking and breast cancer risk among Chinese female.…”
Section: Introductionmentioning
confidence: 89%
“…After reviewing the full text of these studies in detail, a total of 39 articles, involving 100,452 participants from 14 provinces, municipalities and regions, were included in the final review (Appendix 1). Among these included studies, we identified 6 cohort studies (Li et al, 2005;Shannon et al, 2005;Wang et al, 2006;Dai et al, 2010;Pronk et al, 2011;Shrubsole et al, 2011;) and 33 case-control studies (Lu et al, 1992;Xu et al, 1997;Zhao et al, 1999;Tao et al, 2002;Zou et al, 2002;Zhang et al, 2003;Chow et al, 2005;Lee et al, 2005;Chou et al, 2006;Huang et al, 2006;Li et al, 2006;Jin, 2007;Ma, 2007;Zhang et al, 2007;Kallianpur et al, 2008;Ren, 2008;Wang et al, 2008;Shrubsole et al, 2009;Wang et al, 2009;Zhang et al, 2009;Qian et al, 2010;Shi et al, 2010;Bao et al, 2011;Dai et al, 2011;Leu et al, 2011;Zhang et al, 2011;Hou et al, 2012;Xu et al, 2012;Yu et al, 2012;Wang et al, 2013). According to the NOS items, 11 studies were evaluated as high quality, 25 studies as modest quality, and 3 studies as low quality, respectively.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…[15] Depending on this association, some studies further focused on psychological factors in relation to the elevated risk of specific cancer. [1617181920] To demonstrate the relationship between stress and cancer, a population-based sample of 3177 cancer-free adults were followed for 24 years with findings suggesting that major depression was associated with a higher hazard for overall cancer (hazard ratio [HR]: 1.9, 95% confidence interval [CI]: 1.2-3.0) and a significant increased hazard for breast cancer (HR: 4.4, 95% CI: 1.08-17.6). [17] A study followed 33,819 newly diagnosed major depressive disorder (MDD) patients with mean duration of 5.19 years, and the result showed that female MDD patients had higher breast cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…[19] A study investigated the relations of perceived stress and lifestyle to breast cancer and found perceived stress, when combined with potentially risky lifestyle behaviors, may be a contributing factor to breast cancer. [20] As presented above, psychological factors are known to contribute to breast carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, although stressful events were not proved to be a direct cause of cancer, in our opinion, they might promote or even accelerate the development of a preexisting malignancy. And actually another recent study suggests that perceived stress may be a contributing factor to breast cancer, when combined with potentially risky lifestyle behaviors [14].…”
mentioning
confidence: 99%